1983
DOI: 10.1177/0148607183007004381
|View full text |Cite
|
Sign up to set email alerts
|

Studies in the Use of the Intraperitoneal Route for Parenteral Nutrition in the Rat

Abstract: The effects of intraperitoneal administration of normal saline, dextrose, and amino acids were studied in a rat model for intraperitoneal alimentation. No adverse effects from the use of placement of an intraperitoneal catheter were found. Animals who received amino acids demonstrated a specific metabolic advantage over animals who received isocaloric amounts of carbohydrate. They lost less weight and maintained a higher serum albumin. The intraperitoneal route may provide a relatively simple and efficient met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The ability of the peritoneum to absorb fluids and salts is extensively used in dialysed patients. Studies on animals (4,5,9) showed that the peritoneal cavity may also serve as a route for the administration of nutrients. Dextrose and amino acid solutions were found to be highly absorbable by the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of the peritoneum to absorb fluids and salts is extensively used in dialysed patients. Studies on animals (4,5,9) showed that the peritoneal cavity may also serve as a route for the administration of nutrients. Dextrose and amino acid solutions were found to be highly absorbable by the peritoneum.…”
Section: Discussionmentioning
confidence: 99%
“…Intraperitoneal delivery in animals provides a relatively simple and efficient route to study parenteral nutrition in humans. 96 In HAR, mouse pups received L-leucine (1.5 μg/g, Sigma, L6914), or L-isoleucine (0.6 μg/g, Sigma, I5281), or L-valine (2.4 μg/g, Sigma, V4638) from P7 to P9. The dose was estimated based on circulating levels of these amino acids in mice: L-leucine (∼200μM), 97 L-isoleucine (80-100μM), 97 , 98 and L-valine (200-400μM).…”
Section: Methodsmentioning
confidence: 99%